Evaluasi Program Keluarga Harapan (PKH) di Desa Kadugenep Kabupaten Serang - Alvin Muntako Jaelani; Figo Sakifli Rahmatulloh; Indri Febriyanti; Putri Cecilia (Peneliti.net, 2022)
Poverty is a social problem that gets special attention in the world. The problem of poverty in developing countries is a fairly complex problem because it often still occurs. In Indonesia itself, the problem of poverty is a social problem that is always worthy and interesting to be studied further. One of the benchmarks for the progress of a country is the number of poor people in the country. To overcome the problem of poverty and empower the poor in Indonesia, the government has developed and implemented various programs. Specifically for social security issues, especially poverty problems, the government created the Family Hope Program (PKH). The Family Hope Program (PKH) in Kadugenep Village has not run well in accordance with the objectives launched by PKH, namely to improve and advance the standard of living for beneficiary families. The implementation of the PKH program in Kadugenep Village still needs to be addressed.